Characterization of potential probiotic in digestive tract of Mugil cephalus (Linnaeus, 1758) - Firdus Firdus; Cut Putri Fhatalina; Lenni Fitri (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2022)
Probiotics are beneficial microbes in living things that are useful for improving the balance of microbes in the digestive tract and have a positive influence on the physiology and healthiness of the host. This study aimed to obtain bacterial isolates that could be used as probiotics from striped mullet (Mugil cephalus) and to characterize it macroscopically, microscopically, and biochemically. Isolation of probiotic bacteria was carried out using the spread plate method. The medium used to isolate probiotic bacteria was MRSA (De Man Rogose Sharpe Agar) medium. The probiotic test was carried out by hydrolysis of starch and casein. The diversity of bacterial morphology was observed based on macroscopic, microscopic, and biochemical tests. A total of 2 probiotic bacteria (PIB 1 and PIB 2) were obtained. The characterization results showed that the two probiotic bacteria belonged to the Gram-positive bacteria, in the form of bacilli which had different colony morphology. The results of morphological and biochemical tests indicated that one bacterial isolate belonged to the genus Bacillus (PIB 1) and the other isolate belonged to the genus Lactobacillus (PIB 2).